Moving beyond storytelling emerging research in microfinance - Watkins, Todd A.; Hicks, Karen (Contemporary studies in economic and financial analysis, 2009)
Despite the promise for international development, and despite the proven track record of exceptional loan repayment rates, little research has explored the impact this expansion has had on global poverty and economic and social development in general. This title outlines a multidisciplinary research agenda for the field.